Survey on Weighted Load Balanced Routing Protocol and Energy-Aware Routing Protocol for MANET (International Journal of Engineering and Computer Science, 2014)
AODV  is  a  prominent    routing   protocol   for MANET  that  uses hop  count  as  a  path  selection  metric. However, AODV has no means to convey traffic load on current route. In this paper we will survey  protocols  for load-balancing and energy-aware routing on MANET .  This protocol is used for Internet gateway broadcasting route, and it evaluates route with node’s residual energy and transmission load. With this protocol node accessing Internet can find a shortest route and avoid low-power node and busy node. The routing    strategy   in   this   paper    focuses   on distributing  the  traffic  on  the  routes  consisting  of  nodes with  comparatively longer  life and have less traffic  to pass through. Aggregate Interface   Queue Length (AIQL), to deal with traffic issue.   The  weight  of a  route  is  decided  by  three factors:   the  aggregate   interface   queue  length,   the  route energy  and  the  hop count.  The route with highest weight value     is    selected     for     further      data     transmission.